Salinity tolerance of three Salix species: Survival, biomass yield and allocation, and biochemical efficiencies. (October 2017) - Major, John E.; Mosseler, Alex; Malcolm, John W.; Heartz, Shane
Abstract: Salinity tolerance is an important adaptive trait for land reclamation, particularly after petroleum extraction from the Athabasca oil sands "gigaproject" in western Canada. We compared survival, biomass yield and allocation, and biochemical efficiency for three willow species: Salix discolor (DIS), S. eriocephala (ERI), and S. interior (INT) grown under control (CTL) and medium and high salinity treatments (MST and HST, target EC = 1.5 and 3.0 mS cm −1, respectively). In HST, all DIS and ERI plants died, but 33% of INT plants survived. For DIS and ERI, total aboveground (AG) dry mass decreased from CTL to MST, whereas for INT, AG dry mass increased slightly in MST and also increased further in HST. Stem length was not influenced by salinity treatment; however, there was a significant treatment x species interaction for basal diameter resulting from a basal diameter decrease in DIS and ERI and increase in INT with increasing salinity. Maximum rate of carboxylation and electron transport showed equal or greater values for DIS and ERI in MST compared with CTL, but INT displayed a greater stimulation (1.3x) in the MST and HST. Across species and salinity treatments, corresponding biochemical efficiency traits showed a significant positive relationship to total AG dry mass, strongly supporting the theory of sink regulation of photosynthetic capacity. All final biomass and survival traits had significant genotype or genotype x salinity treatment interactions, but only one such effect was found for biochemical efficiency traits. The saline tolerance of INT may be due to natural selection in the arid regions of the southwest USA, where it is thought to have its evolutionary origins. Highlights: Examined salinity tolerance in Salix discolor (DIS), S. eriocephala (ERI), and S. interior (INT). DIS and ERI responded negatively to increased soil salinity. INT had greater saline tolerance and leaf biochemical efficiencies. Biomass was significant for species, genotype, species x salinity, and genotype x salinity. Leaf biochemical efficiency traits showed significant relationships with biomass yield.